A Novel Polysaccharide Isolated From Fresh Longan (Dimocarpus longan Lour.) Activates Macrophage via TLR2/4-Mediated PI3/AKT and MyD88/TRAF6 Pathways - Lan, Haibo; Li, Wu; Xu, Jucai; Yang, Yuzhe; Tan, Zhaolun; Yang, Ruili (Frontiers in Pharmacology, 2021)
A novel immunomodulatory polysaccharide (LP4) with a molecular weight 6.31×104 g/mol was purified from fresh longan pulp. It was composed of glucose, mannose, galactose, glucuronic acid, xylose, arabinose, galacturonic acid, fucose, and rhamnose in a molar percentage of 36:31:10:7:4:4:3:2:2, and mainly linked by (1→6)-β-Man, (1→4)-β-Glc and (1→6)-α-Glc. LP4 can obviously enhance the phagocytosis of macrophages and promote the proliferation of lymphocytes. After treating macrophages with LP4 (12.5~50 µg/mL), the production of IL-1β and TNF-α was significantly increased. These increases of cytokines were suppressed when the TLR2/TLR4 receptors were inhibited by anti-TLR2 and/or anti-TLR4 antibodies. Moreover, the mRNA expression of INOS, AKT, PI3K, TRAF6 and MyD88 was significantly suppressed by TLR2/TLR4 antibodies. These results indicated that LP4 induced macrophage activation mainly via the TLR2 and TLR4-induced PI3K/AKT and MyD88/TRAF6 pathways.